Separation of Rights and Obligations (Spin-Off) Sharia Business Unit PT. Bank Sulselbar - Ummu Kaltsum; Asyari Hasan; Rahmat Ali (Budapest International Research and Critics University, 2022)
This study examines the Sharia Business Unit at PT Bank Sulsebar, as a conventional bank that seeks to spin-off (separation of rights and obligations) into the Sharia Business Unit (UUS) from the aspect of mechanism, readiness, business model and benefits. This study applies a qualitative research model with a phenomenological approach and case studies. The results of the study revealed that the separation of rights and obligations of the sharia business unit of PT. Bank Sulselbar uses a pure spin-off model through ascertaining the spin-off model, constructing spin-off stages, creating spin-off scenarios, providing and meeting capital, and determining the composition of shareholders. PT. Bank Sulselbar starts from improving the quality of human resources, product differentiation, technology development and product and network innovation, as well as implementing good corporate governance. Spin-Off Benefits PT. There are two Bank Sulselbar, namely for the development of sharia business, and for the parent and subsidiary.